Patients must be encouraged to 'Talk Hypos'. (January 2015) - Jensen, Klaus H
Klaus Jensen* speaks to Daphne Boulicault, Commissioning Editor: A Copenhagen native, Klaus Henning Jensen started his career working as a medical doctor in a hospital setting. An entrepreneur at heart, he drew from his background in physics and business administration to co-found a device company – successfully developing a new type of surgical screw for osteosynthesis of hip fractures. Klaus' career at Novo Nordisk spans almost a decade and is rooted in Global Medical Affairs. He has held a series of Medical Director and Vice President roles with responsibilities cutting across the entire Novo Nordisk (UK and Ireland) diabetes portfolio – medical devices, Victoza ® (liraglutide), Tresiba ® (insulin degludec), Ryzodeg ® (insulin degludec/insulin aspart) and Xultophy ® (insulin degludec/liraglutide), as well as other GLP-1 and insulin treatments – with medical and scientific responsibility for the R&D of several of these products. He now sits on the UK & Ireland leadership team as Head of Clinical, Medical and Regulatory.